Decomposing niche components reveals simultaneous effects of opposite deterministic processes structuring alpine small mammal assembly - Song, Wen-Yu; Onditi, Kenneth Otieno; Li, Xue-You; Chen, Zhong-Zheng; He, Shui-Wang; Li, Quan; Jiang, Xue-Long (Frontiers in Ecology and Evolution, 2023)
Introduction Species distribution in alpine areas is constrained by multiple abiotic and biotic stressors. This leads to discrepant assembly patterns between different locations and study objects as opposite niche-based processes—limiting similarity and habitat filtering—simultaneously structure communities, masking overall patterns. We aimed to address how these processes structure small mammal communities in the alpine tree line transition zone, one of the most distinct vegetation transitions between alpine and montane habitats. Methods We compiled a dataset of species checklist, phylogeny, and functional traits from field collection and published sources spanning 18 mountains in southwest China. We first examined hypothetical niche-based processes with frequently used phylogenetic and trait approaches using this dataset. The species traits were decomposed into different niche components to explore the respective effects of specific stressors. Indices representing evolutionary history, trait space, and pairwise species distance were estimated and compared with null model expectations. Linear mixed-effect models were used to assess the association patterns between diversity indices and elevation. Results The results indicated that phylogenetic and functional richness were positively correlated with species richness. In contrast, distance-based indices were either negatively or weakly positively correlated with species richness. Null model analyses suggested no evidence of non-random phylogenetic or overall trait patterns. However, the resource acquisition niche tended to be more overdispersed (positive slopes), while the habitat affinity niche tended to be more clustered (negative slopes) beyond the high elevation tree line. Discussion These findings show that opposite niche-based processes simultaneously structure small mammal communities in alpine areas. Overall, the present study provides vital insights into the complexity of assembly processes in these habitats. It also highlights the importance of relating relevant traits to distinguish the influences of specific abiotic and biotic stressors.